Entangled Trajectories Based on Wigner Function with Negative Values (Journal of Atomic and Molecular Sciences, 2016)
Wigner function is a fundamental method to study the connection betweenquantum and classical system. Since negative value can be accepted by Wigner functioneven from a positive initial condition, they are various issues existing in correspondinginterpretation as well as the development of numerical methods. We presentthe entangled trajectories based on the Wigner distributions with negative values.
Keywords: Entangled trajectory; Wigner function.